Assessment of the application for renewal of the authorisation of Amaferm® (fermentation product of Aspergillus oryzae NRRL 458) as a feed additive for dairy cows. (18th February 2020) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kos Durjava, Mojca; Kouba, Maryline; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: AMAFERM ® is a fermentation product produced by Aspergillus oryzae NRRL 458, containing alpha‐amylase and cellulase enzyme activities, authorised for use as a feed additive for cows. This scientific opinion concerns the renewal of the authorisation of this additive for its use in dairy cows. In its former opinion, the EFSA Panel on Additives and Product or Substances used in Animal Feed (FEEDAP), based on the data and knowledge available at that time, concluded that the additive is safe for cows, for the consumers and the environment. In that assessment, the Panel also concluded that the additive is non‐irritant or a dermal sensitiser but should be considered a potential respiratory sensitiser. The applicant provided new information regarding the characterisation of the additive in terms of enzyme activities as well as information concerning the production strain. Regarding the enzyme activities in the fermentation product, weaknesses and limitations in the methods of analysis were noted. The information regarding the production strain did not permit to confirm its taxonomic classification, moreover uncertainty remains regarding the presence of viable cells/spores in the final product. Therefore, the FEEDAP Panel could not confirm the previously drawn conclusions regarding the safety of the production strain and consequently could not confirm the safety for the target species and consumers. There was no need for assessing the efficacy of the additive in the context of the renewal of the authorisation.